Algarve hotel price determinants: A hedonic pricing model - Soler-García, Ismael Pablo; Gemar-Castillo, Germán; Correia, Marisol B.; Serra, Francisco (Elsevier, 2019)
This study sought to assess customers' willingness to pay for a wide variety of characteristics and attributes of hotels in Portugal's Algarve region. After collecting nearly all the information available on TripAdvisor for hotels in this region, a hedonic pricing model was developed using a database of 9992 cases. The results suggest that – after standardisation – the most important variable shaping Algarve hotel room rates is the previous day's prices. When associated with a family-friendly hotel, star category and services have a greater value than beaches or golf courses do. Customers also appreciate some types of hotels, such as boutique, quaint or trendy hotels, but view others negatively, such as family-friendly or business hotels. Only the specific location of Falesia Beach adds value, although the Algarve is a desirable destination overall. Both destination and hotel managers can use the proposed method to analyse data for their region on customers' propensity to pay.
Keywords: Hostelería - Precios - Gestión - Algarve (Portugal); The Algarve; Hotel; Pricing management; Hedonic; Brand image management